Dental Arch Dimensions in Patients with Mild, Moderate and Severe Hypodontia and a Control Group - Khalaf, Khaled (International Journal of Innovative Research in Medical Science, 2016)
Objectives: To compare maxillary and mandibular dental arch dimensions between subjects with mild, moderate and severe hypodontia and a control group. Method and Materials: The study comprised 120 patients with hypodontia divided into three groups of 40 mild (≤2 teeth congenitally missing), 40 moderate (3-5 teeth congenitally missing) and 40 severe (≥6 teeth congenitally missing) hypodontia; and 40 age and sex matched controls. Maxillary and mandibular dental arch lengths, widths and depths were recorded on study models using digital callipers and compared between all hypodontia and control groups using Two-way ANOVA and Bonferroni's post-hoc tests of subgroup comparison. Results: Two-way ANOVA revealed patients with hypodontia had significantly smaller maxillary and mandibular dental arch dimensions compared with controls (p<0.05). Furthermore, patients with severe hypodontia demonstrated smaller dental arch dimensions than those in the mild and moderate hypodontia subgroups, but the differences were statistically significant only between the severe and mild hypodontia subgroups (p<0.05). The most affected dental arch dimension in all hypodontia groups was the maxillary dental arch depth. Conclusions: Patients with hypodontia had smaller dental arch dimensions than control. Reduction in dental arch dimensions appeared to be affected by the degree of hypodontia, with severe hypodontia having the greatest effect followed in descending order by moderate and mild hypodontia. The findings of this study will help to improve our clinical practice during the multidisciplinary management of this complex condition.